American foundations and their fields. - American Foundations Information Service; Raymond Rich Associates; Twentieth Century Fund. (New York American Foundations Information Service, 1997)
Irregular.
Vol. 7 accompanied by the Twentieth Century Fund; 1939-48, by the Raymond Rich Associates.
Vols. for 1931-34 issued by the Twentieth Century Fund; 1939-48, by the Raymond Rich Associates.
Keywords: Endowments -- United States -- Directories